Examination of Harmonics in Incandescent Lamps and CFLs - (:unkn) unknown (LONDON SCIENCE PUBLISHING LTD, 2010)
Compact fluorescent lamps (CFL) are widely used in lighting technology since they have less power consumption and more efficiency compared with incandescent lamps. They require neither external ballast nor a starter. Therefore they are less sized, more economic and more aesthetical than fluorescent lamps. However, if they're used in big quantity in the installation, it may cause some power quality problems. In this paper, incandescent lamps and energy saving compact fluorescent lamps are compared by means of their electrical, optical data and their total harmonic distortion (THD). Their advantages and disadvantages are emphasized Power factor correction methods for electronic ballasts are discussed and their cost effectiveness is compared.
Keywords: Compact Fluorescent lamp; harmonics; incandescent lamps